Optimalisasi Perilaku Hidup Bersih dan Sehat pada Siswa Sekolah Dasar - Ibnu Phonna Nurdin; Raysa Zilva Nabila; Nessa Rahayu; Lilis Kartina; Rahmat Mubaraq; Zulfan Zulfan; Asnika Putri Simanjuntak; Mutiara Fitri; Syafira Aulia Rangganis; Rianti Putri; Bella Billiant J Ananta Kembaren; Riki Yulianda (Jurnal Medika: Medika, 2025)
Children's problems in maintaining cleanliness and health still face significant challenges. Therefore, handling is needed, one of which is socialization, to build awareness of clean and healthy living among children (PHBS). PHBS is a crucial step in shaping Indonesia's future golden generation. This service was carried out in November 2024 at Madrasah Ibtidaiyah Negeri 11 Rukoh, Banda Aceh City. The participants in this clean and healthy environment socialization activity are 38 students. The purpose of this socialization is to raise awareness about the importance of maintaining environmental cleanliness in schools by involving students. The materials covered in the socialization are washing hands with soap and clean water, consuming healthy and nutritious food, disposing of waste in designated areas, maintaining toilet cleanliness, and exercising regularly. The results of the service show that the majority of elementary school students already understand and have practiced these positive activities. Two-way communication is well-established. This is demonstrated by the enthusiasm of the students in listening, answering, and providing positive feedback on this activity. Therefore, this service activity was successfully carried out and yielded good results for the students' ability to maintain a healthy and clean lifestyle, both at school and when at their respective homes.